Asymmetric Price Transmission of Red Chili Market in North Sumatra Province, Indonesia - Terkelin Surbakti; Tavi Supriana; Iskandarini Iskandarini (Agro Bali : Agricultural Journal, 2022)
The high disparity in red chili prices between producer prices and consumer prices indicates that farmers and consumers do not benefit from the red chili trade, due to the long marketing channels and market power of intermediaries. Prices that fluctuate and do not reflect actual market conditions indicate the inefficiency of marketing agents is called asymmetric price transmission. This study aims to analyze the transmission pattern of red chili prices from producer to consumer level in North Sumatra Province. The analytical model used in this study is the Asymmetric Error Correction Model (AECM). The data used is secondary data that is systematically recorded in the form of monthly time series data from 2016-2020. The results showed that the price transmission between red chili marketing institutions in North Sumatra Province is asymmetric in the short term and long term in the wholesale-producer and wholesale-consumer relationships.